Artificial Neural Networks in Predicting the Number of New Students using the Backprobapication Method : (Case Study: Santo Thomas Catholic University Medan) - Alex Rikki; Doni El Rezen Purba; Marulak Lasron Siahaan; Petrus Leonardi Marpaung; Reni Maria Manalu (Jurnal Mantik, 2022)
An artificial neural network is an information processing designed by imitating how the human brain works in solving problems, namely by carrying out the learning process. Backpropagation is one of the algorithms of artificial neural networks that is often used in predicting because it has a good level of accuracy. Uncertainty in the number of registrants at the Catholic University of Santo Thomas, forecasts or predictions are made. The problem formulation of this research is "How to predict new student admissions using an Artificial Neural Network with the Backpropagation method?". The purpose of this study is to find out how many new students there will be in 2022 in order to plan a strategy to find out the ups and downs of the number of new students.